Answer 1. If we look at the denominators first we see the sequence 1, 2, 3, 4,... It makes sense to start this sequence at *n* = 1. In order for the first term to be positive and the terms to alternate sign, we must multiply by (-1)^{n + 1}. The general term of the sequence, starting at *n* = 1, is Answer 2. If we look at the signs first we see 1,-1,1,-1,.... This can be described by (-1)^{n}, starting at *n* = 0. Then the denominator of the *n*^{th} term is (*n* + 1). The general term, starting at *n* = 0, is | |